Ethical path for human rights protection in the digital society - Wang Yuwei; Wang Huiwen; Pei Zhaobin (SHS Web of Conferences, 2023)
In the digital age, digital survival has become an important part of the basic way of life, and produced a series of digital situation related human rights protection requirements, including equal use of digital technology without discrimination, from the use of digital technology, from the use of digital technology manipulation of people, as well as the personal digital information and property autonomy, etc. In the face of increasingly professional and strong control of digital technology, the digital age of human rights protection not only need the government to establish regulation digital technology development and application of laws and regulations, establish professional relief agencies to regulate data companies and online social platform, provide effective relief to help digital vulnerable groups, and requires the development and use of digital technology and network social platform to strengthen self-discipline, and establish everyone must abide by the digital technology application ethics.